Las TIC y el aprendizaje en niños de preparatoria en la escuela “Dr. Miguel Moreno Ordóñez” periodo académico 2023 - 2024 - Toro Tinoco, Cinthya Madeleyne (2024)
The objective of this research work was to analyze learning through the implementation of ICT in high school children at the Dr. Miguel Moreno Ordóñez School with a qualitative descriptive approach accompanied by the analytical and synthetic, non-experimental cross-sectional method, since that the collection of information was thoroughly described clearly and precisely without making inferences. A non-probabilistic sampling was applied because the population is very small, therefore an interview consisting of 5 open questions was carried out with 2 teachers from the educational establishment, revealing that the majority of them have had experience with the use of ICT but There are difficulties such as little manipulation of them due to the limitation of digital resources and tools in the real context of the students; After these results, an observation guide with 5 items was applied to 11 students. These data allowed us to obtain more concrete results, highlighting that the children show little familiarity with ICT, however, when using one of the digital tools they show motivation and interest. to learn and carry out activities within classes. When analyzing and interpreting the results, it was concluded that the use of ICT at the preparatory sublevel reveals a complex scenario. The findings described underline the importance of effectively and comprehensively addressing the challenges linked to training and teacher support regarding the correct use of ICT. ICT, with the aim of enhancing its benefits and promoting innovative teaching, promoting collaboration and communication in the educational environment. That is why the need arises to develop an integrative proposal based on a guide of five activities as teaching support with work activities oriented towards the feasible integration of ICT. Keywords: Learning, methodology, tools, teaching, difficulties.